“I Am Unable to Build Myself as an Anthropologist”: Interview with the Honorable Teacher-Artist Giselda Hernández Ramírez - Amado González, Miguel Angel (2024)
The interview contained in this work is part of a set of reflections collected during several meetings with honorable professors-artists of the Master's Degree in Formative Processes of the Teaching of the Arts in Cuba. Below, you can read in full the contributions of Doctor of Science Giselda Hernández Ramírez, a controversial teacher for the resolute bravery through which she assumes her positions regarding the most complex cultural processes. Guided by a series of questions, the interviewee refers to notions such as cultural normalization, creative process, Anthropology(s), among others. Their contributions to the scientific literature, the very particular criteria on the teaching-learning of Anthropology in Cuba, and the absolute commitment from/to artistic and pedagogical training stand out.